P101 Hepatitis A screening and susceptibility in men who have sex( MSM) with men: an unintended benefit of PrEP. (16th June 2022) - Gouda, Mahmoud; Fitzpatrick, Colin; Williams, Debbie; Siddiq, Mohammed
Abstract : Background: Hepatitis A virus(HAV) is a sexually transmitted enteric infection in MSM. 70% vaccination levels in MSM is required to achieve adequate herd immunity. Access to PrEP has driven increased numbers of MSM to sexual health clinics for other sexual health interventions including hepatitis A testing/vaccination. Aims & Method We aimed to determine if hepatitis A testing has increased since access to HIV PREP became freely available in England, and if susceptibility to hepatitis A has decreased by comparing hepatitis A testing and susceptibility of MSM attending for the first time to our sexual health service in May-October 2019 with MSM attending for the first time in May-October 2021. Results: 588 MSM attended for the first time in the study period(372 in 2019, 216 in 2021). The median age was 31(IQR=25-42) years old. MSM were significantly more likely to be tested for hepatitis A in 2021 than 2019 (93%.v.56%, p=0.0001). Susceptibility to hepatitis A amongst MSM did not change between in 2021 compared with 2019 (48%.v.47%, p=0.921). MSM who were susceptible were significantly younger (median-age=27(IQR=23-36) than those where were immune (median-age=33(IQR=27-45), p<0.05. There were 91/96(95%) MSM who were invited to return for vaccination and in 64/96(67%) vaccination was initiated in the study period. Discussion: It is likely that provision of HIV-PrEP has increased hepatitis A testing among MSM, however newly attending MSM continue to have inadequate levels of immunity to hepatitis A. Innovative strategies are needed to broaden opportunities for earlier Hepatitis A vaccination before MSM attend sexual health clinics.